Analisis Swot Usaha Sektor Informal di Pasar Amlapura Timur Kabupaten Karangasem pada Era Pandemi Covid-19 - Ni Putu Suciyawati; I Wayan Suwendra (Ekuitas: Jurnal Pendidikan Ekonomi, 2022)
This study aims to find out 1) SWOT analysis of informal sector businesses in the East Amlapura market in the era of the covid-19 pandemic when viewed from strengths, weaknesses, opportunities, and threats; 2) SWOT analysis of informal sector businesses in the East Amlapura market during the COVID-19 pandemic era when viewed from the right strategy used. The type of research used is descriptive qualitative. The subjects of this study were 50 informal business traders in East Amlapura. While the object of the research is a SWOT analysis of informal sector businesses in the East Amlapura market. Methods of data collection using interviews, questionnaire, and documentation. The data analysis technique used descriptive analysis. The result of this research is the Internal Strategy Factor Matrix, it can be seen that the total value of strength is 2.6 while the total value of weakness is 1.36. This shows that the strength factor of informal traders in the East Amlapura Market in the era of the covid-19 pandemic is greater than the weakness factor of traders. The External Strategy Factor Matrix shows that the total score for opportunities is 2.2, while the total score for threats is 1.65. This shows that the opportunities for informal traders in the East Amlapura Market in the era of the covid-19 pandemic are greater than the threat factor faced by informal traders in the East Amlapura Market. The results of the SWOT calculation get the results of the X horizontal axis of 2.4 and the Y vertical axis of 0.55. Based on these numbers, it can be concluded that the position is in quadrant I because both results are positive.